38.1: Invited Paper: High Performance Deep Red Three‐Unit Tandem OLEDs for Automotive Lighting Applications. (24th February 2021) - Pang, Huiqing; Xie, Menglan; Gao, Liang; Lu, Nannan; Wang, Qiang; Ding, Hualong; Kwong, Ray; Xia, Sean
Abstract : We report high performance deep red tandem OLEDs suitable for automotive lighting applications. We developed a deep red phosphorescent emitter that has an intrinsic photoluminescent (PL) peak wavelength at 639 nm and a photoluminescent quantum yield PLQY of 0.80. A low‐voltage red host (LVRH) material was developed to match this emitter, which enables a single‐unit, bottom emission device to reach 2, 000 cd/m 2 with an external quantum efficiency (EQE) of 25.8%, bias voltage of 3.7 V, and LT95 of 6, 000 hrs. A 3‐unit device incorporating this emissive system along with a novel charge‐generation layer (CGL) was fabricated and its device structure was optimized by tuning the hole transport layer (HTL) thickness. The device achieved a current efficiency of 39 cd/A, overall EQE of 77%, LT95 of 46, 000 hrs, and bias voltage of 9.9 V at 2, 000 cd/m 2 . This tandem device also reaches a deep red chromaticity with a peak wavelength of 641 nm, and CIE (X, Y) = (0.706, 0.293). The LT95 of the same device at 85 °C was 9, 700 hr at 2, 000 cd/m 2 . Such a deep red OLED is desirable for automotive lighting applications.